2020
DOI: 10.1017/s0031182020001213
|View full text |Cite
|
Sign up to set email alerts
|

An efficient photograph-based quantitative method for assessing castrating trematode parasites in bivalve molluscs

Abstract: Parasitic castration of bivalves by trematodes is common, and may significantly reduce the reproductive capacity of ecologically important species. Understanding the intensity of infection is desirable, as it can indicate the time that has passed since infection, and influence the host's physiological and reproductive response. In addition, it is useful to know the developmental stage of the trematode, to understand trematode population trends and reproductive success. However, most existing methods (e.g. visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Jokela et al., 1993; Walker, 2017), particularly for the virulent R. campanula (Müller et al., 2015; Taskinen et al., 1994), but these studies still record native mussels being able to reproduce at low infection intensities. We have also previously recorded gravid mussels at low infection intensities of R. campanula (Brian & Aldridge, 2021), suggesting that understanding the degree of infection is as important as understanding its presence (Brian & Aldridge, 2020). Nevertheless, our results highlight that even intermediate infection intensities are correlated with mussel castration, showing the need to understand the presence and distribution of this highly virulent parasite across individuals and populations.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Jokela et al., 1993; Walker, 2017), particularly for the virulent R. campanula (Müller et al., 2015; Taskinen et al., 1994), but these studies still record native mussels being able to reproduce at low infection intensities. We have also previously recorded gravid mussels at low infection intensities of R. campanula (Brian & Aldridge, 2021), suggesting that understanding the degree of infection is as important as understanding its presence (Brian & Aldridge, 2020). Nevertheless, our results highlight that even intermediate infection intensities are correlated with mussel castration, showing the need to understand the presence and distribution of this highly virulent parasite across individuals and populations.…”
Section: Discussionmentioning
confidence: 87%
“…Error bars represent standard 95% confidence intervals. (c) The average infection intensity (percentage of the gonad filled with trematode tissue, following Brian & Aldridge, 2020) of mussels at BC and OW. Only infected mussels were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased emphasis on invertebrates may facilitate this, especially with the advent of new methods to accurately quantify infection in these hosts (e.g. Brian & Aldridge, 2020). In addition, we have shown that detailed knowledge of parasite life histories is an important but often overlooked aspect of predicting community structure.…”
Section: Discussionmentioning
confidence: 99%
“…Following the removal of gonadal fluid, the mussel was sacrificed by cutting the posterior and anterior adductor muscles and the visceral mass was removed. The gonad was then examined for trematodes and, if present, the percentage of the gonad filled with trematodes was calculated through squashing gonad samples between two slides and calculating the mean trematode area in replicate photographs (Brian & Aldridge, 2020).…”
Section: Methodsmentioning
confidence: 99%